2015
DOI: 10.1093/nar/gkv1002
|View full text |Cite
|
Sign up to set email alerts
|

dbSUPER: a database of super-enhancers in mouse and human genome

Abstract: Super-enhancers are clusters of transcriptional enhancers that drive cell-type-specific gene expression and are crucial to cell identity. Many disease-associated sequence variations are enriched in super-enhancer regions of disease-relevant cell types. Thus, super-enhancers can be used as potential biomarkers for disease diagnosis and therapeutics. Current studies have identified super-enhancers in more than 100 cell types and demonstrated their functional importance. However, a centralized resource to integra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
300
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(314 citation statements)
references
References 51 publications
12
300
2
Order By: Relevance
“…A particularly active subset of REs is situated in super-enhancers (SEs). SEs are large clusters of enhancer elements which show high association for Mediator occupancy and histone H3K27Ac modifications, and they show more tissue specific activity than enhancers in general [1214]. As we and others have reported, we found that candidate risk SNPs often overlap SEs, and may especially affect disease predisposition.…”
Section: Resultssupporting
confidence: 66%
“…A particularly active subset of REs is situated in super-enhancers (SEs). SEs are large clusters of enhancer elements which show high association for Mediator occupancy and histone H3K27Ac modifications, and they show more tissue specific activity than enhancers in general [1214]. As we and others have reported, we found that candidate risk SNPs often overlap SEs, and may especially affect disease predisposition.…”
Section: Resultssupporting
confidence: 66%
“…Accordingly, this region matches an S-E domain predicted by profiling K27ac ChIP-seq signals in the interactive database DBsuper [101] (Figure S11). Integrating ChIP-seq signals for additional trans-factors (such as Mediator complex, BRD4 and RNA Pol II) and active histone marks (e.g., K4me2/3) may strengthen such S-E predictions [102].…”
Section: Resultssupporting
confidence: 57%
“…To investigate this hypothesis using our dataset, we overlaid the genomic positions with a database of 65,950 super enhancers across 107 tumor and normal cell types 26 . In the majority of TERTp structural variants (65%), at least one predicted super enhancer was found to directly overlap with the juxtaposed position (Supplementary Table 3).…”
Section: Resultsmentioning
confidence: 99%